Dry Sliding Wear Properties and Microstructure of 7075 Aluminum Alloy via Plasma Electrolytic Oxidation - SHI Yuan-ji, LI Jun-wan, GUO Xun-zhong, YU Lin-hui, LI Shuang, HUANG Hao (Cailiao Baohu)
In this paper, 7075 aluminum alloy were treated in silicate-borate based electrolyte via plasma electrolytic oxidation(PEO), employing a pulsed constant voltage power mode to improve the surface quality and surface properties of 7075 aluminum alloy.The effects of electrical parameter(duty cycle)on morphology and wearing behavior of the PEO coatings were thoroughly investigated.The surface and cross section morphology of the coatings was observed by scanning electron microscope.Besides, the wearing properties of the coatings were evaluated by the wearing experiment.Results showed that the microhardness and the wearing resistance of the coatings both first increased and then decreased with the increase of duty cycle.Composition analysis proved the coating was composed of α-Al2O3 and γ-Al2O3.